The impacts of complexity on knowledge management processes: Why does information science contribute to conscious capitalism? - Damian, Ieda Pelógia Martins; Santos, Beatriz Rosa Pinhairo [UNESP] (IGI Global, 2021)
Knowledge management has already determined its true importance and stands as a consistent, necessary, present, and concurrently futuristic process in the physical and digital environments where people are present. In the transitional economic, social, cultural, and technological contexts, given the anguish of establishing or not the information and knowledge society, it is purely remarkable that informational conflicts happen in a devastating manner, negatively affecting the producers, recipients, and makers of this world: people. Many refute the efficiency and effectiveness of the knowledge management process, with the justification that managing knowledge is impossible, since it is not palpable. On the other hand, there are those who argue that knowledge management is a process composed of activities that aim to make possible the production, availability and sharing of consistent, effective, functional, and true knowledge in environments, in order to make it available for better decision-making, since before it became known, it was necessary to deal with data and information. Therefore, knowledge management does not deal with autocracy, as it is a democratic, conscious process that is committed to the truth and that fights against misinformation, as well as against false news that contributes to people's authoritarianism, ignorance, and inferiority, precisely because untrue information will be assimilated and will result in malicious knowledge. For Edgar Morin, who defends the theory of complexity, the classic thinking of science is based on three pillars, among them order, separability, and reason. What can be inferred is that the excess of reason can become blind to the point that subjective aspects, which are also part of the process of transforming objectivity, suffer a certain negation. In addition, order and separability, during all these years, have also been responsible for the lack of synergy and interdependence that exists in corporations, organizations, social networks and people's homes. It may even sound strange to say that there is no synergy and interdependence in social networks, but this statement is precisely defended when visualizing the loneliness and despair established in these environments, justified by the eternal and constant search for acceptance and belonging, which most of the times do not becomes contemplated. Also, according to the author Edgar Morin, complex thinking does not aim to replace separability with inseparability but defends a dialogical relationship that uses separability in an inseparable context, that is, that calls for responsible action by all sectors of society here already mentioned: economic, social, cultural, scientific, and technological. Thus, this chapter aims to approach the concept of knowledge management from a more expansive perspective, which is not only in the business sphere, based on the complexity theory. As a hypothesis, having knowledge management as a concept originating from information science, the author argues that this is a scientific field that contributes to a more conscious capitalism in consumption and informational production, even because it is necessary for the control of other types of consumption, as private, public, essential, and superfluous, among others. To address the aspects of complexity in knowledge management and reflect on the referred hypothesis, a qualitative and bibliographic research was carried out.